TiO2–WO3 core–shell inverse opal structure with enhanced electrochromic performance in NIR region. Issue 31 (30th July 2018) - Ling, Han; Yeo, Loo Pin; Wang, Zhiwei; Li, Xianglin; Mandler, Daniel; Magdassi, Shlomo; Tok, Alfred Iing Yoong
Abstract : A novel core–shell TiO2 –aWO3 inverse opal structure was fabricated with significantly enhanced electrochromic long term reversibility in NIR region. Abstract : More than 50% of solar energy comes from the infrared region (as radiant heat) of the solar spectrum. Electrochromic (EC) materials, which can dynamically modulate the transmittance of infrared (IR) radiation, can be effectively applied in smart windows for thermal management in buildings. In this work, a core–shell TiO2 –WO3 inverse opal (IO) structure was fabricated through the electrodeposition of WO3 onto TiO2 IO templates. The TiO2 IO templates were synthesized by introducing TiO2 into the voids of a polystyrene (PS) colloidal crystal template, followed by calcination to remove the PS microspheres. It was found that the TiO2 –WO3 IO core–shell structure can modulate NIR transmittance at wavelengths from 700 to 1600 nm in the NIR range when potential is applied in LiClO4 /PC electrolyte. When −0.3 V is applied, up to 60% of NIR radiation in this range can be blocked. The NIR transmittance can be modulated by tuning the applied potential. This study focuses on comparing the novel TiO2 –WO3 IO structure with electrodeposited WO3 thin film to fully elucidate the effect of the inverse opal morphology and the TiO2 –WO3 hybrid system on the optical properties. Results show that the NIR blockage can be sustained up to 90% after 1200 reversible cycles for TiO2 –WO3 IO structure. The greater surface area of the IO structure increases the number of active sites available for the redox reactions by providing a larger contact area with the electrolyte. The more electroactive area with improved charge transfer enhances the overall NIR transmittance contrast as compared to bulk WO3 thin film. Furthermore, the addition of WO3 to TiO2 to form a composite has been shown to enhance cycling performance and device lifespan.